Knowledge and attitude towards geriatric and its associated factors among final year medical students of International Islamic University Malaysia - Shalihin, Mohd Shaiful Ehsan; Abd Muttalib, Nuria Syafira; Azmi, Nur Syahirah; Mohd Zin, Zahra Najwa (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Background: The aging population is growing globally causing demographic changes and morbidity. Therefore, in order to improve the elderly's health and provide comprehensive health services, every healthcare personnel should have good knowledge and attitude. This research aims to measure the level of knowledge and attitude towards geriatric and to determine the associated factors among IIUM final year medical students. Methodology: A cross – sectional study was conducted between May to June 2020 during the Movement Control Order (MCO) period among 116 consented students. Structured questionnaires consist of Geriatric Attitude Scale and Palmore Facts on Aging Quiz were completed via online Google Form. Data was analysed using IBM SPSS version 22.0. The association between the categorical variables were analysed using Mann Whitney U test and Kruskal–Wallis test. Results: The data revealed that the overall total knowledge and attitude towards geriatrics among the students was at moderate level with median score of knowledge at 14.00(13.00) and mean score for attitude of 48.52(5.53). Place of residence (P=0.01) and presence of grandparents were the significant (P=0.04) factors that affected the knowledge of the students towards geriatrics. Number of siblings significantly (P=0.05) influenced attitudes of the students towards geriatrics. Conclusion: It was concluded that there is need of improvement for the current geriatric curriculum with more refined implementation of gerontology course in the basic IIUM medical learning. Further research should be conducted to discover more on the factors that affecting knowledge and attitude towards geriatrics among medical students.